Inconsistency in Imposing Sanctions on Drug Abuser with Narcotics Legislation - Pambudi, Pambudi; Riswadi, Riswadi (Yayasan Adra Karima Hubbi, 2024)
The inconsistent imposition of sanctions on drug abuse offenders in Indonesia highlights significant challenges in the enforcement of narcotics legislation. Despite comprehensive regulations, discrepancies persist in the fairness and uniformity of punishments. This research examines these issues by employing a normative juridical method with a statutory and conceptual approach. The study identifies gaps between existing legal provisions and their application, revealing legal loopholes that undermine the objectives of narcotics legislation. Findings indicate that while efforts to enforce strict laws exist, inadequate coordination among law enforcement agencies exacerbates the inconsistency. This research aims to evaluate these discrepancies and propose solutions to strengthen legal frameworks and enforcement mechanisms. By enhancing inter-agency collaboration and revisiting the sanctions framework, the study advocates for a more just and effective legal system to combat drug abuse. These recommendations are expected to bridge gaps in narcotics legislation, ensuring justice for offenders while promoting the rule of law.